Employment protection, capital investments and labor productivity - Johanna Kemper (ETH Zurich, KOF Swiss Economic Institute, 2017)
In this paper, I analyze the effect of Employment Protection Legislation (EPL) on investments in physical capital and labor productivity by exploiting the fact that small establishments in Germany below a given size threshold are exempted from certain parts of EPL. I do this by means of an Regression Discontinuity Design (RDD) and using establishment-level data for the period 1994-2012. Following the implications of the theoretical literature, I also analyze whether or not EPL affects the employment margin and conduct an implicit test for the possibility of a negative impact of EPL on investments due to hold-up by using linked employer-employee data. I do not find a statistically significant threshold effect on any of these outcomes - also not when analyzing the effect of EPL by industry. The results of EPL on investments and labor productivity are consistent with the predictions of the literature that states if EPL does not affect the employment margin, it should also not impact any other margin of non-labor adjustment.
Keywords: J08; J65; J24; 330; Employment protection; investments; labor productivity